The Personnel Security Management in the Personnel Management System of the Enterprise (Economic journal of Lesya Ukrainka Volyn National University, 2018)
The purpose of the article is to improve the theoretical and methodological provisions of personnel securitymanagement in the personnel management system of the enterprise on the basis of a functional approach. The main tasks are: to consider the definition approaches of the personnel security essence; to identify the main functional components of personnel security management; to specify the content and tools for providing personnel security for each of the functional areas. The article deals with approaches to the definition and clarification of the personnel security essence, justified the place and role of personnel security management in the personnel management system. The personnel safety management of the enterprise is considered as a personnel management component aimed at identifying, eliminating and preventing risks and threats that may be caused by personnel and leads to negative consequences for the enterprise, at the same time, provide for the protection of employees, creation of auspicios conditions for work, needs  rovisionand development goals realization. The research uses a functional approach to structuring the components of personnel security management, the main of which are: the needs planning and staffing sources to provide the company with the required number and quality of staff for a specific period, including the selection of applicants for vacancies, adaptation of staff; formation of the optimal staff composition and it’s structure; ensuring equal opportunities and conditions for the rational use and consolidation of staff in accordance with the principles of the scientific organization of labor; redistribution, including professional qualification or job placement of employees as elements of career management, and stabilization of personnel; motivation; development and assessment of personnel; control aimed at eliminating the possibility of causing damage. The effectiveness of personnel security management is ensured by taking into account all aspects and functional areas of personnel management and implementing the personnel security tools in their structure.
Keywords: personnel management, personnel security, personnel security management, functional components of personnel security management